IMPLEMENTASI ALGORITMA NAIVE BAYES PADA SISTEM MONITOR KUALITAS AIR KOLAM LELE BERBASIS IOT - Setiono, Nur Syahad; Utomo, Yudo Bismo; Alfin, Ach Arif (LPPM Poltek ST Paul, 2024)
In catfish farming, water quality stability is a key factor as it is considered a crucial parameter for successful catfish cultivation. Several factors influence the pond water quality, such as leftover food, accumulated fish waste, and environmental conditions like rainy or dry seasons. Typically, the replacement of pond water is determined based on visual cues such as water color and odor, relying on rough estimates. Therefore, the author chose the title